Effect of Topical Artemisinin from Artemisia Annua in Comparison with Tacrolimus on Induced Atopic Dermatitis in Mice - Mohammed Fareed Hameed (Journal of Global Pharma Technology, 2020)
Objective: To evaluate the effectiveness of artemisinin isolated from Artemisia annua terpenes fraction in atopic dermatitis mice model. Methods: This research is a randomized, prospective, placebo and controlled animal study. Thirty two male, albino mice included in this study. The mice were randomly divided into four groups (Each group eight). Group I without treatment (Healthy). Group II only the inducer Phthalic anhydride given. Groups II, III, and IV subjected to 5% phthalic anhydride solution and after three hours of phthalic anhydride application, treatment is used for group III (Tacrolimus 0.03% ointment) , and group IV (Artemisinin 175mg/kg). Artemisinin was extracted from Artemisia annua and isolated by preparative high pressure liquid chromatography. Measurement of serum interleukin 13, interleukin 4, and immunoglobulin E and histopathology were done. Results: When healthy group is compared to atopic dermatitis induced non-treated group, a significant increase (P value ≤ 0.05) in serum IL-13 and IL-4 were found, while high significant increase (P value ≤ 0.001) in serum IgE was recorded. Regarding Histopathology score, high significant decrease in epidermal thickness, hyperkeratosis, parakeratosis, erosion, inflammation and edema after 4 weeks of starting treatment between Tacrolimus and atopic dermatitis induced non-treated groups. When artemisinin and atopic dermatitis induced non-treated groups were compared, a significant decrease was found in serum IgE. Conclusion: Artemisia annua artemisinin has an effect on phthalic anhydride induced atopic dermatitis albino mice like model.Keywords: Atopic dermatitis, Artemisia annua, Artemisinin.